Numerical Study on the Ballistic Impact Response of Aramid Fabric- epoxy Laminated Composites by Armor Piercing Projectile. (2017) - Nayak, N.; Banerjee, A.; Panda, T.R.
Abstract: This paper presents the results from experiments and numerical simulations on the ballistic impact of 10 mm thick aramid fabric-epoxy composite laminates by a 7.62 mm armor piercing projectile at varying impact velocities. Post perforated residual velocity (RV), contact duration of projectile with the target and ballistic limit (BL) of composite were simulated using a finite element code HyperWorks-Radioss. Interaction of projectile with composite laminates was captured by high speed video. The predicted ballistic parameter from simulation compared well with the precision experimental results. The simulated energy and stress distribution during impact of projectile on composite laminate showed marked difference with variation in impact velocities (SV). The magnitude and duration of stress as well as the contact force was found to increase when projectile impacted at lower SV thus enhancing the extent of delaminating and the core damage area and the trend was reversed for higher SV. The findings corroborate the bullet inflicted damage of composite laminates experimentally determined by ultrasonic C-scan.